Evaluation of the Wind Energy Potential in the Coastal Environment of Two Enclosed Seas - Florin Onea; Alina Raileanu; Eugen Rusu (Advances in Meteorology)
The work presents a comprehensive picture of the wind energy potential in the coastal environment of the Black and the Caspian Seas. 10-year of data coming from the US National Centers for Environmental Prediction was considered as the main source. This dataset was subsequently compared with both in situ and remotely sensed measurements. The results show that the western side of the Black Sea has an enhanced wind power potential, especially in the vicinity of the Crimean Peninsula. As regards the Caspian Sea, the northeastern sector can be considered more energetic. A direct comparison of various wind parameters corresponding to the locations with higher potential in the two target areas considered was also carried out, in order to notice the similarities and the key features that could be taken into account in the development of an offshore wind project. Finally, it can be concluded that the coastal environments of the Black and the Caspian Seas can become in the near future promising locations for the wind energy extraction, as well as for the hybrid wind-wave energy farms that could play an important role also in the coastal protection.